Estimating the Societal Benefits of Satellite Instruments: Application to a Break-even Analysis of the GeoXO Hyperspectral IR Sounder - Lauer, Christopher; Conran, Joseph; Adkins, Jeffery (Frontiers in Environmental Science, 2021)
This paper describes the process, and lessons learned in a preliminary benefits study of a proposed infrared hyperspectral sounder (HSS) for NOAA’s next generation geostationary satellite program (GeoXO). The valuation of government-owned satellite systems providing a public good with a complex array of instruments is a nascent field of study. Many different sensor configurations are possible, but there are restrictions due to physical and budget constraints. Accounting for economic considerations during the design and planning phase for satellite constellations helps to ensure that the most cost effective instruments are selected. To assess whether the HSS instrument should be included on GeoXO, we applied a value of information approach and found the benefits associated with this instrument are likely to substantially outweigh the costs. Value of information studies often focus on data and information that has a direct use case. Estimating benefits for the HSS is especially challenging because data are not used directly by decision makers. Instead these data along with information from other Earth observing (EO) satellites play a key role in producing the inputs necessary for modern numerical hydrometeorological modeling. We describe strategies to assess the marginal (i.e., incremental) contribution of an instrument that is part of a complex information production process. We make several recommendations that, if implemented, would improve the quality of future studies of this kind. This includes (1) a systems approach to observing system planning, (2) improving the design of observing system experiments (OSSE and OSE), and (3) better tracking of the decisions and needs of end-users, especially those external to the agency.